Rehabilitation And Upgradation Of An Existing Road Using Fly Ash, An Industrial By Product: A Case Study - Jayanta Kumar Mohanty, Biswajit Jena, Sagarika Panda (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Fly ash a fine powder thrown out in large quantities from thermal power plants as a waste material in a by- product of combustion of pulverized coal. The disposal of fly ash poses a serious problem considering the air, water and soil problems. The solution to this problem lies in its bulk utilization of fly ash at dumping sites. This paper is summarized with brief details of the properties and design aspects of fly ash used in highway embankments. This paper investigates the improvements in the properties of expansive soils, as road subgrade stabilized with lime and fly ash in varying percentages. Laboratory tests were undertaken to study the swelling and strength characteristics of soils stabilized, fly ash and a combination of both. Soil and fly ash were added separately at ranges 0-50%, respectively, compaction, California Bearing Ratio (CBR), free swelling tests were performed on natural and treated soil samples. For the investigated admixture fly ash; comparing the results obtained of the natural and treated samples, the CBR and CS of fly ash treated samples increased significantly, coupled with the swelling reduction, depending on additive content. It could be concluded that stabilization of subgrade soils by fly ash admixture is successful and more economical..